Portuguese Dimension Stones: Sector Characterization and International Market Strategies - Lopes, Luís (2017)
Despite its small size, about 98,000 km2, Portugal presents a huge geological variety that, in what concerns the exploitation of ornamental rocks, results in the production of a great variety of rocks. Among the most internationally known are undoubtedly the high quality marbles produced in the South of the Country, Estremoz Marbles. However, in the last decades the production of ornamental Jurassic limestones, located in the Center of Portugal, has undergone a significant increase both in the variety of rocks produced and volume of production. To these materials are joined the granites, exploited a little throughout the Country, the shales (mainly in the North) and the Cretaceous limestones explored near Lisbon: the stone used in the reconstruction of the Portuguese Capital after the great earthquake of 1 of November 1755 (several varieties of “Lioz” limestone). Quartzite, jasper and volcanic rocks (in the mainland, but mainly in the Atlantic Archipelagos of the Azores and Madeira) are exploited without quantitative expression. In recent years the Worldwide growth of the sector, both as a result of the emergence of new producer countries and the generalized increase production of traditional ones, principally due to the optimization of the exploitation and processing processes, has led to extremely aggressive competition in which the material quality is not a sufficient condition for its assertion in this global market. In an attempt to consolidate the Portuguese offer of ornamental stones and to give credibility to the industry by observing strict rules of quality control, respect for the environment, social protection and contribution to the country's economic development, the Stone.PT brand was created. Is attributed to companies that meet the requirements listed in a detailed and demanding specifications. This brand allows the ensemble presentation, as a strategy of collective efficiency, of the stone Portuguese products produced in the biggest worldwide specialty fairs.